The Role of Students in Developing Education in the Community: Service in Karanggetas Village, Bangodua District, Indramayu Regency - Azizah, Muasromatul (Kusuma: Jurnal Pengabdian kepada Masyarakat, 2024)
The community service program conducted by lecturers and students of IAI Pangeran Dharma Kusuma Segeran Indramayu in Karanggetas Village, Bangodua Subdistrict, Indramayu Regency, lasted for 43 days, from January 15 to February 26, 2023. This program aimed to enhance the quality of education and strengthen the community's social and religious values through various activities held in prayer rooms, mosques, schools, madrasahs, and the KKN (Community Service Program) post. Activities included tutoring, skill training, regular religious studies, and character development. Through a collaborative approach, the service not only had a positive impact on improving education quality but also encouraged active community involvement in social and religious development. This program is expected to raise awareness about the importance of education and foster a more independent, religious, and resilient generation ready to face future challenges.